Breast siliconomas resulting from the injection of liquid silicone - Contreras-Grande, Jheferson (2019)
A previously healthy 65-year-old woman was referred due to breast pain, the physical examination revealed that both breasts were hard on palpation. Mammography revealed multiplate and scattered rounded nodular lesions in both breasts. The ultrasound revealed a snow pattern in both breasts. The patient later recalled to have received an injection of liquid silicone 20 years ago. Siliconomas are the result of a granulomatous reaction to silicone, either due to leakage of implants or due to direct injection. We recommend that in these patients magnetic resonance images should be obtained every year to rule out carcinoma in-situ.